Analysis and comparison of pollution flashover performance of porcelain insulators in distribution system 22 kV - P. Wimonthanasit (2018)
Electrical insulators of the Provincial Electricity Authority (PEA) of medium system are mostly porcelain insulator types that consist of pin type, line post, and pin post insulators. The distribution lines will be polluted by industrial contaminants, salt fog or natural dust. Experience shows that pollution flashover is one of the main natural calamities harming and affecting the voltage stability and reliability of distribution system. This paper compares the test results obtained from the artificial pollution tests according to IEC 60507 in the chamber for tests with standard porcelain insulators consist, pin post, line post and pin type insulators of medium system under same test conditions. The salt fog test results indicate that the pollution flashover performance of pin type insulator is less than to 50 percent of wet power frequency withstand voltage at equivalent salt deposit density (ESDD) = 0.5 mg/cm2 and the leakage current (LC) of pin type insulator increased to 11.4 mA at ESDD = 0.5 mg/cm2 at nominal voltage. In the experiment indicate that AC pollution flashover performance of pin post insulator has better than line post and pin type insulators in the serious pollution area. This data will be useful to be guideline for solving problems and reducing power loss from leakage current on the surface of the insulators as a result of surface dirt and pollution. Moreover, it will be useful to select or design suitable insulators for using in places with salt conditions, high rainfall, high wind speeds and high humidity. © (2013) Trans Tech Publications, Switzerland.